Дослідження показників епілептичних ЕЕГ-сигналів за допомогою методів нелінійної динаміки - Білошицька, Оксана Костянтинівна; Клименко, Тетяна Андріївна (НТУ "ХПІ", 2017)
Горизонт прогнозування поведінки нелінійних динамічних систем досить незначний. Доведено, що епілептичні напади характеризуються збільшенням хаотичної складової, отже завчасне виявлення тенденцiй до такого збiльшення дозволяє прогнозувати розвиток патологiй та погiршення стану людини. В данiй роботi розглядаються методи нелінійної динаміки, які дозволяють точно охарактеризувати періоди діяльності мозку при епілепсії. Для аналізу ЕЕГ-сигналів використовувалися показник Херста та фрактальна розмірність. Результати отриманих досліджень можуть бути використані в подальшому для побудови моделі прогнозування нападiв епiлепсiї за допомогою ЕЕГ.

Biological systems are complicated structures and reveal the specific features that refer to the chaotic behavior. Being the quantity reflection of brain activity, EEG contains components that refer to neither periodic signal nor to the artifacts. The evidence of such chaotic features significantly increase during the epileptic seizures that are not predictable and rather dangerous for patients. The horizon of prognosis for nonlinear dynamical systems is limited and this fact evokes the need for complicated approach for solving the task of timely detection of patological activity in brain. In our work we used two methods of nonlinear dynamic: Hurst exponent and fractal analysis in order to define whether they can be used to distinguish stages of epileptical activity. Hurst exponent estimates the tendency of further behavior and fractal dimension reflects the system complexity. Both this parameters highly correlate with the chaotic behavior. The results demonstrate significant difference for periods of EEG with epilepsy and this parametrs can be used for further enhancement of EEG analysis.
Analysis of the parameters of EEG signals with epileptic activity using nonlinear methods
Keywords: нелінійна динаміка; ЕЕГ; R/S-аналіз; показник Херста; фрактальна розмірність; nonlinear dynamics; EEG; RS analysis; Hurst exponent; fractal dimension